2020
DOI: 10.1080/02656736.2020.1766705
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ablation of CT ‘invisible’ liver tumors using MRI fusion: a case control study

Abstract: Purpose: To evaluate whether 'invisible' liver tumors on CT can be treated by stereotactic radiofrequency ablation (SRFA) using fusion of pre-ablation MRI. Methods: In this retrospective case-control study, 60 patients (14 with Hepatocellular carcinoma (HCC) and 46 with metastatic liver tumors) with CT 'invisible' lesions underwent SRFA using MRI-fusion between June 2005 and June 2018 ('fusion group'). For comparison, 60 patients who underwent SRFA without image fusion were selected using nearest neighbor prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
(50 reference statements)
1
22
1
Order By: Relevance
“…Moreover, no significant difference was observed in the local recurrence rate between the two groups 1 month after RFA. Similarly, other studies have shown that the difference in recurrence is small during early follow-up, but it tends to be significant in late followups [25].…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, no significant difference was observed in the local recurrence rate between the two groups 1 month after RFA. Similarly, other studies have shown that the difference in recurrence is small during early follow-up, but it tends to be significant in late followups [25].…”
Section: Discussionmentioning
confidence: 56%
“…Multiple trajectories are planned with the 3D navigation system software on multiplanar reformatted images to cover the entire tumor volume with an appropriate peritumoral safety margin. If required, especially for non-visible lesions in the planning CT, it is possible to fuse pre-interventional CT/MRI/PET/SPECT data with the intraprocedural CT dataset [26]. Following registration, accuracy check, and sterile draping, the ATLAS aiming device (Interventional Systems Inc., Kitzbühel, Austria) is adjusted using the 3D navigation system.…”
Section: The Technique For Srfamentioning
confidence: 99%
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
“…Four propensity score matched analyses compared stereotactic thermal ablation for different subtypes of patients or lesions. Stereotactic RFA yielded similar safety and treatment e cacy outcomes when comparing CT 'invisible' tumours ablated with MR image fusion to CT visible tumours (30), octogenarians to a younger study population (36), lesions in a subphrenic location to non-dome locations (39) and HCC in a subcardiac position to a non-subcardiac location (40).…”
Section: Comparative Studiesmentioning
confidence: 90%